Are doctors and nurses associated with coverage of essential health services in developing countries? A cross-sectional study - de Pinho Helen; Prescott Marta R; Kruk Margaret E; Galea Sandro (BMC, 2009)
Abstract Background There is broad policy consensus that a shortage of doctors and nurses is a key constraint to increasing utilization of essential health services important for achieving the health Millennium Development Goals. However there is limited research on the quantitative links between health workers and service coverage rates. We examined the relationship between doctor and nurse concentrations and utilization rates of five essential health services in developing countries. Methods We performed cross-national analyses of low- and middle-income countries by means of ordinary least squares regression with coverage rates of antenatal care, attended delivery, caesarean section, measles immunization, tuberculosis case diagnosis and care for acute respiratory infection as outcomes. Doctor, nurse and aggregate health worker (sum of doctors and nurses) concentrations were the main explanatory variables. Results Nurses were associated with utilization of skilled birth attendants (P = 0.02) and doctors were associated with measles immunization rates (P = 0.01) in separate adjusted analyses. Aggregate health workers were associated with the utilization of skilled birth attendants (P < 0.01) and measles immunization (P < 0.01). Doctors, nurses and aggregate health workers were not associated with the remaining four services. Conclusion A range of health system and population-level factors aside from health workers influences coverage of health services in developing countries. However, it is also plausible that health workers who are neither doctors nor nurses, such as clinical officers and community health workers, may be providing a substantial proportion of health services. The human resources for health research agenda should be expanded beyond doctors and nurses.